SIFAT KIMIA TANAH PADA BERBAGAI ZONASI HUTAN MANGROVE DI DESA TUMPAPA KECAMATAN BALINGGI KABUPATEN PARIGI MOUTONG - Nursin, Armin; Wardah, Wardah; Yusran, Yusran (Universitas Tadulako, 2014)
A study was conducted to determine soil chemical properties in zonation of mangrove forest, Tumpapa village, Balinggi district, Parigi Moutong regency, Central Sulawesi.We measured these effects by quantifying some chemical soil analysis were done on soil samples taken at depths 0-60cm. Soil samples were collected from the field by using paralon cylinders at four different zonation; transition zone (Rhizophora apiculata, Bruguiera, Ceriops and Xylocarpus), high tidal zone (Rhizophora apiculata and Bruguiera gymnorhiza), middle tidal zone (Rhizophora apiculata) and low tidal zone (Rhizophora styllosa and Rhizophora mucronata), respectively. The results showed that chemical soil properties in transition zone were pH 7.2, C-organic 0.75%, total N 0.13%, available P 8.68% and cation exchange capacities 22.17 me/100 g. At the high tidal zone were pH 6.4, C-organic 2.46%, total N 0.27%, available P 9.14% and cation exchange capacities 24.16 me/100 g. At the middle tidal zone were pH 6.1, C-organic 2.55%, total N 0.26%, available P 9.32% and cation exchange capacities 24.54 me/100 g. Hence, At the low tidal zone were pH 6.7, C-organic 1.71%, total N 0.15%, available P 10.41% and cation exchange capacities 23.11 me/100 g. Keywords : Zonation, Mangrove forest, Soil chemical properties.